A protocol for the integration of multi-omics bioinformatics: Mechanism of acupuncture as an adjunctive therapy for alcohol use disorder - Zhang, Peiming; Lan, Xiaochang; Fan, Baochao; Chen, Yiming; Wei, Xiaojing; Li, Xiangli; Fan, Ni; Tang, Chunzhi; Lu, Liming (Frontiers in Neurology, 2023)
Background: Alcohol use disorder (AUD) has become a significant factor in the global disease burden. As a non-pharmacological therapy, certain therapeutic potential has been found in acupuncture, but in-depth mechanism studies related to acupuncture for AUD are still insufficient. Methods: Based on a randomized control design and a multi-omics analysis plan, this protocol detailed the recruitment (42 AUD patients), the group allocation (21 in acupuncture group vs 21 in sham acupuncture group), the intervention and the follow-up (replacement drugs as usual treatment, 2-week acupuncture duration, and 3-month follow-up), and the data collection and analytical processes. As the statistic plan, (1) for the clinical outcomes, in addition to the time required for alcohol withdrawal symptoms to subside as the primary outcome, changes in the alcohol withdrawal symptoms, alcohol withdrawal craving, mood dysfunction, sleep disorder, fatigue, self-efficacy, gastrointestinal symptoms and the quality of life, and the relapse outcomes will be compared to assess differences between the groups by independent sample t-test, with significance if P-value<0.05 (two-sided); (2) for the gut microbiome, α-diversity analysis will be used for biodiversity, and β-diversity analysis and microbial multivariate analysis will be used for comparing biological environments and seeking differential Microbes; as for the fecal metabolomics, the combination of multivariate analysis and univdariate analysis will be appiled to found the differential metabolites, and metabolic pathway enrichment analysis will also be implemented; (3) for the joint analysis, omics will be conjoint through expression correlation analysis and pathway mapping, to shed light on the microbiome-gut-host effects of acupuncutre as an adjunctive therapy for AUD; and feature screening algorithms combined with tree model will be tried to screen the critical independent variables (e.g. psychiatric symptoms, gastrointestinal symptoms, interventions and gut microbiome and metabomics, etc.) and evaluate their weights of influence on each clinical variables responsing to acupuncture. Discussion: The results of this study may help to strengthen the clinical mechanism evidence of acupuncture intervention in AUD through understanding the regulatory mechanism of acupuncture in the gut microbiome and its metabolism - AUD clinical manifestations.